Fabrication of a Micro-Electromechanical System-Based Acetone Gas Sensor Using CeO2 Nanodot-Decorated WO3 Nanowires - Yuan, Kaiping; Wang, Cheng-Yu; Zhu, Li-Yuan; Cao, Qi; Yang, Jia-He; Li, Xiao-Xi; Huang, Wei; Wang, Yuan-Yuan; Lu, Hong-Liang; Zhang, David Wei (ACS applied materials & interfaces, 2020)
Preparation of reliable, stable, and highly responsive gas-sensing devices for the detection of acetone has been considered to be a key issue for the development of accurate disease diagnosis systems via exhaled breath. In this paper, novel CeO2 nanodot-decorated WO3 nanowires are successfully synthesized through a sequential hydrothermal and thermolysis process. Such CeO2 nanodot-decorated WO3 nanowires exhibited a remarkable enhancement in acetone-sensing performance based on a miniaturized micro-electromechanical system device, which affords high response (S = 1.30–500 ppb, 1.62–2.5 ppm), low detection limit (500 ppb), and superior selectivity toward acetone. The improved performance of the acetone sensor is likely to be originated from the fast carrier transportation of WO3 nanowires, the formation of WO3–CeO2 heterojunctions, and the existence of large amounts of oxygen vacancies in CeO2. The improved reaction thermodynamics and sensing mechanisms have also been revealed by the specific band alignment and X-ray photoelectron spectroscopy analysis.